Galaxy and Mass Assembly (GAMA): galaxy pairwise velocity dispersion. Issue Volume 11:Issue S308(2015) (12th October 2016) - Loveday, Jon; Christodoulou, Leonidas; ,
Abstract: We describe preliminary measurements of the pairwise velocity dispersion (PVD) of galaxies in the Galaxy and Mass Assembly (GAMA) survey as a function of projected separation and galaxy luminosity. Due to the faint magnitude limit ( r < 19.8) and highly-complete spectroscopic sampling of the GAMA survey, we are able to measure the PVD to smaller scales and for lower-luminosity galaxies than previous SDSS-based work. We see no strong scale-dependence at most luminosities in the quasi-linear regime. We observe an apparent drop in PVD towards very small scales (below ≈ 0.1 h −1 Mpc), but this could in part be due to a restriction of the streaming model employed. At intermediate scales, the PVD is highest ( 500 km/s) at intermediate luminosities, dropping at both fainter and brighter luminosities.